SINTESIS SENYAWA KALSIUM FOSFAT DENGAN TEKNIK PRESIPITASI SINGLE DROP - I.P. Ramadani (Jurnal Biofisika, 2012)
The high damage of bone  triggers  a variety  of research  about bone biomaterial. So far, compliance for this needed done import materials. The material which used for bone  biomaterial  is calcium  phosphate.  In  this  research  used  synthesis  of  calcium phosphate.  Synthesis  of  calcium  phosphate  performed  using  precipitation  method single drop and wise drop at room temperature with sintering themperature 900 oC, themperature 70oC with sintering time  variation (110oC, 300oC, 600oC, and 900oC). Results obtained from sintering are  fluffy white powder. Result from x-ray diffraction characteristic  for  all  sample  with  themperature  sintering  900o C  show  the  phase formed  is  calcium  pyrophosphate  and  other  phase  from  calcium  phosphate  that  is hydroxyapatite,  tricalcium  phosphate,  octacalcium  phosphate,  carbonate  apatite type-A  and  carbonated  apatite  type-B.  The  longer  stirring  time  is  so  the  phase  of calcium  pyrophosphate  formed  the  less.  Reaction  themperature  is  very  effect  in formation of  phase  calcium  pyrophosphate,  because calcium  pyrophosphate  which the resulting in room themperature is more than in themperature 70 oC. Beside that precursor  compound  that  has  not  reacted  in  themperature  70oC  less  from  room themperature,  this  is  because  precursor  compound  is  faster  when  heated.  In sintering variation  themperature 110oC and 300oC the precursor formed is more and the best sintering themperature is 900oC.